Climate policy, resource owners' anticipations and the green paradox: model set-up and empirical considerations. Issue 1 (2nd January 2023) - Schneider, Nicolas
ABSTRACT : With the acceleration of environmental commitments, the Green Paradox has been taking centre stage in the climate debate. In the standard Hotelling (1936) framework, producers may interpret environmental regulations as direct threats to resource scarcity rents. They compensate the future losses of revenues by forward shifting the extraction decision to the present period. In this paper, we defend the intuition behind which the anticipation effects of fossil producers are non-negligible and cannot be ignored by environmental planners. However, facing the conflicting evidence and theoretical underpinnings arising from the most recent literature, we argue that their effective impacts on climate targets tend to be over-estimated and might become smaller under reasonable assumptions and identified conditions. Accordingly, a set of recommendations are provided to internalize such inferences within upcoming climate measures.